Assessment of Organizational Commitment Among Nurses in Fatima Memorial Hospital, Lahore - Ashraf, Amna; Arshad, Hina; Saeed Choudhary, Ahmad; Javed, Laiba; Pari, Khansa; Rehman, Sana-Ur-; Yousaf, Ruhsana (Biological and Clinical Sciences Research Journal, 2025)
Organizational commitment among nurses is a critical determinant of healthcare quality, staff retention, and job satisfaction. In settings with limited resources, such as in Pakistan, evaluating organizational commitment helps address challenges in workforce sustainability and care standards. Objective: To assess the level of organizational commitment, including affective, continuance, and normative commitment, among nurses working at Fatima Memorial Hospital, Lahore. Methods: A descriptive cross-sectional study was conducted at Fatima Memorial Hospital involving 133 registered nurses selected through non-probability convenience sampling. Data were collected using a structured questionnaire based on the Three-Component Model of Organizational Commitment. Descriptive statistics were computed using SPSS version 20. Results: The majority of nurses (81.9%) demonstrated exemplary organizational commitment. Affective commitment emerged as the most prominent domain, indicating strong emotional attachment and a sense of belonging to the organization. Continuance and normative commitments were present at moderate levels, suggesting that while nurses felt a moral and practical obligation to stay, emotional factors played a more significant role in their retention. Conclusion: Nurses at Fatima Memorial Hospital demonstrate high levels of organizational commitment, primarily driven by an emotional connection. Strategic interventions to strengthen affective and normative dimensions, alongside supportive work environments, may enhance nurse retention and performance.